EJBM 2019
DOI: 10.7176/ejbm/11-3-22
|View full text |Cite
|
Sign up to set email alerts
|

Study on Overseas Luxury Consumption of Chinese Consumers —The Moderating Role of Fashion Difference Perception

Abstract: The phenomenon of "inner cold and outer hot" in China's luxury market has attracted the attention of many scholars. Drawing on luxury consumption motivation theory, this article explores the relevant factors influencing Chinese consumers' overseas luxury purchase from multiple dimensions. The results show that three variables, the match degree between country of origins and sales, attached foreign emotional value and the store service, have a positive impact on consumers' attitude towards overseas luxury goods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Instead, this result supports (Tsai, 2005) finding that individualistic consumers exhibit greater levels of congruity with their internal selves than collectivistic consumers. Moreover, this study also supports previous researchers (Chai & Ning, 2019;Lee et al, 2008;Knight & Kim, 2007) who have found an insignificant influence of perception on luxury goods consumption. People who think that luxury products are flashy and overpriced share similar views about how "others" behave.…”
Section: There Is a Significant Relationship Between Perception And C...supporting
confidence: 91%
See 2 more Smart Citations
“…Instead, this result supports (Tsai, 2005) finding that individualistic consumers exhibit greater levels of congruity with their internal selves than collectivistic consumers. Moreover, this study also supports previous researchers (Chai & Ning, 2019;Lee et al, 2008;Knight & Kim, 2007) who have found an insignificant influence of perception on luxury goods consumption. People who think that luxury products are flashy and overpriced share similar views about how "others" behave.…”
Section: There Is a Significant Relationship Between Perception And C...supporting
confidence: 91%
“…Contrarily, according to (Chai & Ning, 2019) study, price fairness perception negatively influences consumers' attitudes toward overseas luxury goods. Their finding suggests that when consumers perceive home prices to be comparatively higher than those in foreign countries, indicating a sense of unfairness, their inclination to purchase luxury goods from abroad increases proportionally to their favourable attitudes towards overseas luxuries.…”
Section: The Relationship Between Perception and Consumption Of Luxur...mentioning
confidence: 98%
See 1 more Smart Citation